Open Access to Scientific Information in Emerging Countries - Schöpfel, Joachim (D-Lib magazine, 2017)
Covers the demand for open access in the developing world, with a focus on the five emerging countries, called BRICS - Brazil, Russia, India, China and South Africa. Looks at specific conditions in each country, relying on data from information professionals and scientists from BRICS, with an empirical approach focused on country-specific characteristics and challenges. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.